2013
DOI: 10.1542/peds.2013-0242
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Therapy for Pediatric Functional Abdominal Pain: A Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Pediatric functional abdominal pain is common and costly. Cognitive behavior therapy (CBT) is a promising treatment for these complaints, but solid evidence for its effectiveness is lacking. WHAT THIS STUDY ADDS:This randomized controlled trial shows that CBT reduces abdominal pain in 60% of children 1 year after treatment. Six sessions of CBT delivered by trained master' s students in psychology were equally effective as 6 visits to an experienced pediatrician. abstract OBJECTIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(158 citation statements)
references
References 40 publications
6
146
1
5
Order By: Relevance
“…31 An RCT on individual CBT published shortly after the literature search for the present systematic review showed improvement in 60% of children with FAP after CBT, but the results did not differ compared with standard care (including 6 supportive sessions with the pediatric gastroenterologist). 71 However, children receiving CBT reported significantly fewer symptoms of anxiety or depression compared with children receiving standard care.…”
Section: Alternative Medicinementioning
confidence: 98%
“…31 An RCT on individual CBT published shortly after the literature search for the present systematic review showed improvement in 60% of children with FAP after CBT, but the results did not differ compared with standard care (including 6 supportive sessions with the pediatric gastroenterologist). 71 However, children receiving CBT reported significantly fewer symptoms of anxiety or depression compared with children receiving standard care.…”
Section: Alternative Medicinementioning
confidence: 98%
“…(57) Similar CBT approaches have also been shown to improve pain and sleep disturbances in other pediatric populations. (58, 59) Additional promising psychosocial interventions for youth with IBD include hypnotherapy(60) and mindfulness-based techniques(61) which both can improve mood, pain and HRQoL.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…In practice, outpatient treatments for chronic pain emphasize a rehabilitative approach including decreasing pain-related disability, and it has been a common dictum among clinicians that “improvement is first measured by increased functioning” [38, p. 262]. In research including clinical trials, pain intensity typically has been identified as the primary treatment outcome; however, there is an increasing focus on demonstrating functional improvement as well as pain reduction [17,35] as recommended by leading pediatric pain experts [23]. However, there is a challenge to providers in the clinic setting to assure patients that increased function in the absence of pain reduction is a positive sign, and that functional progress should not wait on pain resolution.…”
Section: Introductionmentioning
confidence: 99%